WAYS OF DEALING WITH PRONUNCIATION ERRORS OF EFL LEARNERS IN SCHOOL - Bayzakova Akhzhibek ,; Kudaibergenova M.R, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
Learning a language is a long process, during which the student inevitably makes a lot of mistakes. It is no secret that even native speakers make mistakes in speech, and foreign language learners, regardless of their desire, make mistakes both in oral and written speech. From the point of view of the methodology of teaching a foreign language, mistakes are different, and they also need to be corrected in different ways.